80 THE PROGNOSTIC FACTORS ASSOCIATED WITH LONG-TERM SURVIVAL IN THE PATIENTS WITH SYNCHRONOUS OLIGOMETASTATIC ESOPHAGEAL ADENOCARCINOMA. (17th September 2021) - Iwatsuki, Masaaki; Harada, Kazuto; Baba, Hideo; Ajani, Jaffer
Abstract:  : Patients with gastrointestinal cancer are increasingly being diagnosed with oligometastatic disease due to the development of sensitive imaging. Oligometastases (OLM) represent a clinical and anatomical manifestation of resistant localized cancer and/or metastases. However, oligometastatic disease is complicated by the lack of uniformity due to the heterogeneity of cancer, therefore, differing prognoses. The aim of this study is to identify the factors associated with long-term survival in the patients with synchronous oligometastatic esophageal adenocarcinoma (EAC). Methods: Between 2002 and 2016, of 1400 patients with EAC (esophagus and Siewert types I and II) treated at our institute, 233 patients initially diagnosed with stage IVB were enrolled. OLM was defined as only metastasized to one organ and less than 5 metastases. We retrospectively analyzed the association between clinicopathological factors and prognosis, especially focused on the pattern of metastases. Results: Eighty-five patients (36.5%) had OLM, and 148 (63.5%) had non-oligometastais (Non-OLM). The patients in OLM had significantly better overall survival (OS) than the patients in Non-OLM (p = 0.0001). Univariate analysis showed pattern of metastases (lymphatic OLM) and treatment method (consolidative local radiotherapy: CLT) were significantly associated with prognosis (p = 0.04 and 0.01). Multivariate analysis revealed that lymph node metastases (cN0-N1), number of metastasis (solitary) and treatment (CLT) were independent predictors for OS of patients with OLM. (p = 0.03, 0.01 and 0.001). In OLM patients, the patients with lymphatic OLM who received CLT had more favorable prognosis (5-years survival rate 25%). Conclusion: This study suggests that CLT is one of the promising modalities for oligometastatic patients with EAC, especially the patients with lymphatic OLM.